Mechanics of fluids - Potter, Merle C. (Cengage, 2017)
The authors use proven learning tools to help students visualize many difficult-to-understand aspects of fluid mechanics. The book presents numerous phenomena that are often not discussed in other books, such as entrance flows, the difference between wakes and separated regions, free-stream fluctuations and turbulence, and vorticity.